Relato De Discentes Sobre Os Principais Desafios Do Aprendizado De Português Como L2 - SANTOS, Carlos Eduardo De Sousa (Universidade Federal do Tocantins, 2023)
The present work aims to present a case study on the development of Teaching/Learning in Portuguese for the deaf, through research with deaf university students. Therefore, this monograph shows the possibility of inserting the teaching in Libras of the Portuguese language, making them find meaning inwriting and reading. Most deaf people have many difficulties with writing and reading. From the information obtained, a reflection was carried out on teaching in Libras for more meaningful learning for the deaf. Deaf people who have Librasas their first language (L1) and Portuguese as a second language (L2) are considered bilingual. For the Deaf student to reach this condition, it is necessaryfor schools to offer a bilingual Libras/Portuguese education, using pedagogical methods in a didactic way on the teaching of Portuguese in Libras.